2021
DOI: 10.1371/journal.pone.0255842
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of somatic fusion techniques for the development of HLB tolerant breeding resources employing the Australian finger lime (Citrus australasica)

Abstract: The Australian finger lime is a unique citrus species that has gained importance due to its unique fruit characteristics and perceived tolerance to Huanglongbing (HLB), an often-fatal disease of citrus trees. In this study, we developed allotetraploid finger lime hybrids and cybrids by utilizing somatic cell fusion techniques to fuse diploid ‘OLL8’ sweet orange or ‘Page’ tangelo callus-derived protoplasts with finger lime (FL) mesophyll-derived protoplasts. Six somatic fusions were regenerated from the ‘OLL8’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Numerous citrus varieties are being newly developed to improve citrus quality globally [11][12][13][16][17][18]. However, the quality of many of these varieties has not been objectively evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous citrus varieties are being newly developed to improve citrus quality globally [11][12][13][16][17][18]. However, the quality of many of these varieties has not been objectively evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, confirmation that our somatic hybrids inherited a complete set of genes of P. trifoliata is not sufficient to conclude that all favorable phenotypic traits of trifoliate orange are transmitted to the somatic hybrids. Phenotypic evaluations demonstrated that CTV resistance of P. trifoliata [18], HLB resistance of M. australasica [127], and adaptation to calcareous soils of C. reticulata [18] were successfully inherited in allotetraploid somatic hybrids. Further extensive phenotypic and genomic studies including transcriptome, small RNA, epigenomome, and mobilome should be conducted to understand the implication of inter-generic somatic hybridization in the functional genomic of the somatic hybrids.…”
Section: Implications Of Genomic Instability For Rootstock Breedingmentioning
confidence: 99%
“…Somatic hybrids plants are regenerated through embryogenesis or organogenesis. Plant protoplast fusion has successfully been used to transfer disease resistance and other qualitative traits (Dutt et al, 2021). Indeed, availability of reproducible protoplast isolation, fusion and plant regeneration protocols will open new opportunities for developing new or improving SSA taro cultivars.…”
Section: Introductionmentioning
confidence: 99%